Increasing Production Capacyty And Efficiency Of Fruit Juice And Beverage Small Medium Enterprisess - Arie Febrianto Mulyadi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2015)
ABSTRACT In Batu, 2 SMEs which produce fruit drink and beverage. SMEs